Redefinition of State Apparatuses: AKP's Formal–Informal Networks in the Online Realm. Issue 5 (3rd September 2018) - Irak, Dağhan; Öztürk, Ahmet Erdi
Abstract: In Turkey, especially since 2010, the ruling Justice and Development Party (AKP) has gradually assumed all power within the state. In parallel, it has introduced a hegemonic project widely known as 'New Turkey', redefining state apparatuses through its proprietary web of networks of formal and informal relations. Inclusion in, or exclusion from, these networks is at the sole discretion of leading political actors, and can be considered as a state apparatus in itself, even though it contains elements that are informal or unofficial. All these networks of official and unofficial apparatuses are centred around President Recep Tayyip Erdoğan. The article focuses on the Twitter interactions of 25 key elements of the AKP's web of networks between 2010 and 2016, using Social Network Analysis. In the Turkish context, the use of Twitter as a means of communication is particularly pertinent, as it stands out as a unique channel for democratic discourse. The findings of the research confirm that the Twitter interactions of the 25 official and unofficial state apparatuses, with very few exceptions, constitute a network well-connected to the core, mostly represented by Erdoğan.